Saving behaviour of citrus farmers in Ghana: implications for rural enterprise development. Issue 8 (16th November 2016) - Donkor, Emmanuel; Anane, Evans
ABSTRACT: This article reports on a study that examined the saving behaviour of farmers in southern Ghana, using a sample of 100 citrus farmers. Probit and Tobit models were used in determining the factors that influence farmers' saving behaviours and amount of saved, respectively. The empirical findings showed that age, household size, dependency, marital status, distance to financial institution, transport cost and congestion exerted significant negative impact on farmers' saving behaviours. On the other hand, income, education, and gender tended to promote good saving behaviour. The article concludes that heterogeneity of factors ranging from socio-economic, household assets, and institutional factors greatly stimulate farmers' saving behaviour.